2007
DOI: 10.1007/s11136-007-9228-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergency physicians’ pain judgments: cluster analyses on scenarios of acute abdominal pain

Abstract: Physicians have been found to give lower ratings of patients' pain than do the patients themselves. We hypothesized that the physicians' rating depends not only on the patient's pain rating but also on other cues. We also hypothesized that these cues influence physicians' pain treatment and urgency level. We gave to 52 emergency room physicians in Toulouse, France, 45 scenarios describing patients with acute abdominal pain, representing all combinations of 5 levels of patient's pain rating, 3 levels of behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…The physicians judged patients' pain using the same kind of additive-type rule as that used by the nurses and nurse's aides. These findings are consistent with (a) suggestions by Craig et al (2011) that facial expressions provide the most sensitive information about pain level; (b) findings by Marquié et al (2008) that physicians rated pain by additively combining patient's pain rating, behavioral manifestations of pain, and signs of the severity of the pathology; and (c) findings by Chibnall et al (1997), who showed that medical students combined the reported pain intensity and the medical evidence in an additive fashion.…”
Section: Discussionsupporting
confidence: 92%
“…The physicians judged patients' pain using the same kind of additive-type rule as that used by the nurses and nurse's aides. These findings are consistent with (a) suggestions by Craig et al (2011) that facial expressions provide the most sensitive information about pain level; (b) findings by Marquié et al (2008) that physicians rated pain by additively combining patient's pain rating, behavioral manifestations of pain, and signs of the severity of the pathology; and (c) findings by Chibnall et al (1997), who showed that medical students combined the reported pain intensity and the medical evidence in an additive fashion.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence supports the influence of medical evidence on symptom judgments made by both lay and medical assessors [ 3 , 12 , 15 17 , 27 ]. For example, among the inpatient population, the highest proportions of agreement were found in obstetrics and the lowest in surgery, oncology, and radiotherapy wards [ 3 ].…”
Section: Discussionmentioning
confidence: 97%
“…Congruence between PSRP and caregiver pain evaluation can be taken as a tool to uncover bias moderators in pain assessment (Solomon, 2001). This issue was studied at various pain conditions or settings (Iafrati, 1986; Grossman et al, 1991; Zalon, 1993; Tait and Chibnall, 1994, 1997; Todd et al, 1994; Chibnall and Tait, 1995, 2001; Chibnall et al, 1997, 2000; Bartfield et al, 1997; Marquié et al, 2003, 2007; Igier et al, 2007). In these studies most health operators were involved and lack of congruence was shown to increase with the PSRP severity.…”
Section: Introductionmentioning
confidence: 99%